Melatonin prevents age-related hearing loss in the murin experimental model - Serra, Lucieny Silva Martins (2022)
Objective: The present study aimed to perform a morphological and morphometric analysis of cochlear structures of C57BL/6J mice receiving oral melatonin for a 12-month period. Methods: 32 male C57BL/6J were divided into control and melatonin groups. Control received saline and ethanol solution and melatonin group, 50 L of 10 mg of melatonin/kg/day orally for a 12-month period. After de experiment the animals were sacrificed into a 40% concentration of CO2 chamber, and the blades were morphological and morphometrically analyzed. Results: The melatonin group revealed a higher median density of viable cells (45 ± 10.28 cells/100 m2, 31---73, vs. 32 ± 7.47 cells/100 m2, 25---48). The median area of stria vascularis was 55.0 ± 12.27 cells/100 m2 (38---80) in the control, and 59.0 ± 16.13 cells/100 m2 (40---134) in the melatonin group. The morphometric analysis of the spiral ligament reveals a higher median of total viable neurons in the melatonin (41 ± 7.47 cells/100 m2, 27---60) than in the control group (31 ± 5.68 cells/100 m2, 21---44). Conclusion: Although melatonin is a potent antioxidant, it does not completely neutralize the occurrence of presbycusis; however, it may delay the onset of this condition.